The Effective Control Strategy in Gunung Lingai Village due to Extreme Flood with SWOT Approach - Santi Yatnikasari; Sigiet Haryo Pranoto; Pitoyo Pitoyo (LPPI Universitas Muhammadiyah Kalimantan Timur (UMKT), 2020)
Samarinda is the capital of the East Kalimantan, which remains troubled by flood risk. The flooding phenomenon happens not only during the rainy season. Some areas in the city of Samarinda are flooded in the rain with a period of 3 hours. This research aims to establish the causes of flooding in Gunung Lingai Village, as then flood control techniques can be implemented. Gunung Lingai Village has been chosen because it is a location with a history of extreme flooding in the town of Samarinda with an area of ​​432.93 Ha. There are 851 flood-affected households from 1390 households with a duration of further than 7 days. This research was carried out with the combination of qualitative and quantitative approaches. Data collection was carried out by combining literature study and secondary data with factual studies to obtain primary data and in-depth interviews with flood-affected communities (mixed method). The status of the flood variables which became the baseline was that of 9 June 2019 and that of 22 May 2020. The results showed that there were two main factors causing flooding, namely natural factors and human factors. A vulnerability of social indicator was established to describe the actual condition, which was complex interaction among drainage system and public welfare. In addition, a SWOT analysis was performed on one of the selected representatives to verify the strategies on flood control system.